Pengelolaan Kurikulum dan Pembelajaran Kimia Berbasis ISO 9001:2008 di SMK Negeri 2 Wonogiri - Tardi, Tardi; , Dr. Eko Supriyanto, S.H, M.H; , Dr. Maryadi, M.A (2017)
The objectives of this study are: (1) To describe the learning planning of chemistry based on ISO 9001: 2008 in SMK Negeri 2 Wonogiri. (2) To describe the implementation of chemistry learning based on ISO 9001: 2008 in SMK Negeri 2 Wonogiri. (3) To describe evaluation of curriculum and learning of chemistry based on ISO 9001: 2008 in SMK Negeri 2 Wonogiri. The type of this research is qualitative research with ethnography design which implemented in SMK Negeri 2 Wonogiri. Data collection techniques with in-depth interviews, documentation, and observation. Data analysis using interactive analysis model with three stages. The results of the research are (1) Planning of chemistry learning based on ISO 9001: 2008 in SMK Negeri 2 Wonogiri, in the preparation of instructional administration documents include effective weekly breakdown, annual program, semester program and syllabus study prepared by curriculum development team, Learning Implementation Plan (RPP ) Developed from the syllabus prepared by subject teachers incorporated in the school level MGMP. An ISO-based chemistry learning plan should always be continually perfected according to the condition and characteristics of the learners. (2) The implementation of chemistry learning based on ISO 9001: 2008 emphasizes on the process of forming learners' learning experiences through face-to-face or laboratory practice. The learning implementation activities include preliminary activities, core activities and closing. Learning oriented to the activities of learners that emphasizes the mastery of knowledge, attitude changes and improving the skills of learners (3) Evaluation of the implementation of learning chemistry based on ISO 9001: 2008 in SMK Negeri 2 implemented through academic supervision by the Principal and assessment of external audit team, where The need for curriculum management and learning is done continuous improvement. Keywords: planning, implementation, evaluation, learning chemistry